Modelling and Experimental Verification of a Solar Reactor for the Photo-Fenton Treatment - Farias, Jorgelina (2010)
In the present work, a novel design of a solar reactor is presented. This pilot plant scale reactor uses the UV-Visible and Near-Infrared solar radiation to promote the photo-Fenton treatment. A theoretical study and experimental verification were performed using formic acid as a model pollutant. The radiative transfer, thermal energy and mass balances equations were solved to compute the formic acid (F) and hydrogen peroxide (P) concentrations as a function of time. The spectral and broadband solar radiation incident on the reactor window was calculated from a computational code: the SMARTS2 program. Statistical estimators have been used to measure the departure of theoretical model from experimental data. A good agreement for formic acid and hydrogen peroxide concentrations, temperature and total and UV broadband solar radiation was obtained. The normalized root mean square errors (NRMSE) of the model for predicted variables were lower than 11%.